Educational Strategy on Sexually Transmitted Infections in Adolescents, San Juan y Martínez - Estévez Mitjans, Dra. Yusmary; Duarte Hernandez, Dra. Keilan; Lorenzo-Orama, Dra. Yarielys; Puente Colombe, Lic. Magaly (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: Worldwide there is an upward trend in the occurrence of sexually transmitted infections, including the immunodeficiency virus AIDS, at the expense of a shift of sexual intercourse to younger and younger ages. Objective: To determine the level of knowledge about sexually transmitted infections (STIs) in adolescents from the ESBU José de la Luz y Caballero in the municipality of San Juan y Martínez during the period from September 2021 to July 2023. Method: An experimental quantitative-qualitative cross-sectional intervention study was conducted from September 2021 to July 2023. The universe consisted of 246 students, a sample of 225 students selected through a simple random sampling to which a questionnaire was applied. The study was conducted in three stages, diagnosis, intervention, and evaluation. Results: In this study, 15-year-old adolescents predominated and females had a higher incidence. A level of knowledge about sexually transmitted infections, including the AIDS immunodeficiency virus, was evidenced; the symptoms and signs, as well as the measures we should take to protect ourselves from STIs at the beginning of the educational intervention, were low in terms of knowledge and at the end satisfactory levels were reached. Conclusions: after applying the intervention, a significant increase in students' knowledge about STIs was achieved, so the intervention was considered effective